Technological Pedagogical Content Knowledge (TPACK): An Overview Through Self-Efficacy and Motivation to Become a Professional Teacher - Everhard Markiano Solissa; Farizawati Farizawati; Mumu Muzayyin Maq; Fauzi Aldina; Hasyim Mahmud Wantu (Universitas Muhammadiyah Enrekang, 2023)
This research is motivated by the importance of Technological Pedagogical Content Knowledge (TPACK) for Becoming a Professional Teacher. The purpose of this study was to examine and analyze the effect of self-efficacy and motivation on TPACK to become professional teachers. This research uses a quantitative approach with a survey method. The sampling technique used purposive sampling of 100 teachers. The instruments used were observation, questionnaires and questionnaires. The data analysis technique used is the classical assumption, correlation analysis, and multiple linear regression analysis including hypothesis testing T test, F test and R2 test. The results of this study indicate: 1) Self-efficacy has a positive and significant effect on Technological Pedagogical Content Knowledge (TPACK), 2) Motivation has a positive and significant effect on Technological Pedagogical Content Knowledge (TPACK), and 3) Self- efficacy and motivation have a positive effect and significant to Technological Pedagogical Content Knowledge (TPACK). The findings of this study indicate the importance of self-efficacy and motivation in improving Technological Pedagogical Content Knowledge (TPACK) to become professional teachers.